ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN LKPD BERBASIS PROBLEM SOLVING UNTUK PESERTA DIDIK MAN 04 PESISIR SELATAN - Lila Ayu, Marta; Yogica, Relsas (Universitas Cokroaminoto Palopo, 2024)
The aim of this research is to determine the obstacles faced by teachers and students during the learning process. This type of research is qualitative in descriptive form. The samples used were biology teachers and 42 students of Phase E MAN 4 Pesisir Selatan. The results obtained in this research were: 1) students' difficulties in understanding biology material, especially abstract material such as virus, 2) The learning media available in schools has not been able to support optimal understanding, as evidenced by the low level of active involvement of students and the completeness of learning outcomes.